2013
DOI: 10.1308/rcsann.2013.95.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary exercise testing as a predictor of complications in oesophagogastric cancer surgery

Abstract: NHS Greater Glasgow and Clyde, UKABstRAct INTRODUCTION An anaerobic threshold (AT) of <11ml/min/kg can identify patients at high risk of cardiopulmonary complications after major surgery. The aim of this study was to assess the value of cardiopulmonary exercise testing (CPET) in predicting cardiopulmonary complications in high risk patients undergoing oesophagogastric cancer resection. METHODS Between March 2008 and October 2010, 108 patients (83 men, 25 women) with a median age of 66 years (range: 38-84 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 14 publications
4
61
1
3
Order By: Relevance
“…One recent study has shown a correlation between AT and the development of cardiopulmonary complications (CPCs), with CPCs occurring in 42% of patients with an AT of less than 9 mL/min/kg compared with 29% of patients with an AT of greater than 9 mL/min/kg but less than 11 mL/min/kg, and 20% of patients with an AT of greater than 11 mL/min/kg. 43 Both peak (VO 2peak ) 44 and maximum (VO 2max ) 45 oxygen uptake Anesthesia for Esophagectomy have also been shown to correlate with CPCs, with one study concluding that a VO 2max of 800 mL/min/m 2 allows esophagectomy to be safely performed. 45 Snowden and colleagues 46 showed that an anaerobic threshold of less than 10.1 mL/kg/min was an independent predictor of increased postoperative complications in major surgery.…”
Section: Carney and Dickinsonmentioning
confidence: 99%
See 1 more Smart Citation
“…One recent study has shown a correlation between AT and the development of cardiopulmonary complications (CPCs), with CPCs occurring in 42% of patients with an AT of less than 9 mL/min/kg compared with 29% of patients with an AT of greater than 9 mL/min/kg but less than 11 mL/min/kg, and 20% of patients with an AT of greater than 11 mL/min/kg. 43 Both peak (VO 2peak ) 44 and maximum (VO 2max ) 45 oxygen uptake Anesthesia for Esophagectomy have also been shown to correlate with CPCs, with one study concluding that a VO 2max of 800 mL/min/m 2 allows esophagectomy to be safely performed. 45 Snowden and colleagues 46 showed that an anaerobic threshold of less than 10.1 mL/kg/min was an independent predictor of increased postoperative complications in major surgery.…”
Section: Carney and Dickinsonmentioning
confidence: 99%
“…45 Snowden and colleagues 46 showed that an anaerobic threshold of less than 10.1 mL/kg/min was an independent predictor of increased postoperative complications in major surgery. Based on these 3 articles, 43,45,46 the following CPET values are proposed as predictive of significant postoperative complications in esophagectomy.…”
Section: Carney and Dickinsonmentioning
confidence: 99%
“…Moyes et al [30] and Yanni et al [31] have shown that upper gastrointestinal surgery for patients and an anaerobic threshold <11 ml/min/kg were associated with the development of cardiopulmonary complications and a trend towards a higher unplanned rate of intensive care admission. Although resource-intensive, CPET could be an additional test in quantifying cardiopulmonary reserves in elderly patients [30,32]. Several modifiable risk factors included in geriatric assessments have been shown to be predictive of poor outcome [25].…”
Section: Discussionmentioning
confidence: 99%
“…In these instances, a careful history and physical examination along with the judicious use of B-type natriuretic peptide may be useful in detection of cardiac dysfunction [40]. Several studies have shown that cardiopulmonary exercise testing (CPET) may have a role to play in the prediction of adverse cardiopulmonary complications after cancer surgery including esophageal cancer [41][42][43]. In an analysis of over 1000 patients comparing the 6MWT to Peak VO 2 (measured with CPET), the correlation between these two tests in individual patients was poor, with a large standard error of estimate (SEE) [44].…”
Section: Cardiovascular Side Effectsmentioning
confidence: 99%